Genicular Nerve Radiofrequency Ablation for Chronic Knee Joint Pain Using a V-Shaped Active Tip Needle: A Single-Center Retrospective Observational Study - Lo Bianco G; Pugliesi M; Misseri G; Li S; Day M; Schatman ME; Abd-Elsayed A; Yong RJ; Robinson CL (Journal of Pain Research)
Giuliano Lo Bianco,1 Marinella Pugliesi,2 Giovanni Misseri,1 Sean Li,3 Miles Day,4 Michael E Schatman,5,6 Alaa Abd-Elsayed,7 R Jason Yong,8 Christopher L Robinson8 1Anesthesiology and Pain Department, Foundation G. Giglio Cefalù, Palermo, Italy; 2Anestesia, Rianimazione e Terapia del Dolore, Dipartimento Rizzoli Sicilia di Bagheria, Bagheria, Palermo, Italy; 3National Spine & Pain Centers, Shrewsbury, NJ, USA; 4Traweek-Racz Endowed Professor in Pain Research, Department of Anesthesiology, Texas Tech University HSC, Lubbock, TX, USA; 5Department of Anesthesiology, Perioperative Care, and Pain Medicine, NYU Grossman School of Medicine, New York, NY, USA; 6Department of Population Health-Division of Medical Ethics, NYU Grossman School of Medicine, New York, NY, USA; 7Department of Anesthesiology, University of Wisconsin-Madison, Madison, WI, USA; 8Anesthesiology, Perioperative, and Pain Medicine, Harvard Medical School, Brigham and Women’s Hospital, Boston, MA, USACorrespondence: Giuliano Lo Bianco, Anesthesiology and Pain Department Fondazione Istituto G, Giglio Cefalù via Pietrapollastra, Cefalù, Palermo, 90015, Italy, Email giulianolobianco@gmail.comBackground: Chronic knee pain from osteoarthritis (OA) affects a significant proportion of adults over 40. Total knee arthroplasty (TKA) remains the standard for advanced OA, yet up to 20% of patients experience chronic postsurgical pain (CPSP). Genicular nerve radiofrequency ablation (GNRFA) can alleviate pain in those unresponsive to conservative treatments or TKA. However, anatomical variability of the genicular nerves may limit treatment durability. This retrospective, single-center observational study investigated whether using a novel V-shaped active tip needle—which creates larger lesions—could improve outcomes.Methods: Fifty patients with symptomatic knee OA or CPSP, who had a ≥ 50% reduction in pain after diagnostic genicular nerve blocks, underwent GNRFA with a V-shaped active tip needle between September 2020 and January 2022. Pain and function were assessed using the visual analogue scale (VAS) at rest and during movement, Western Ontario and McMaster Universities Arthritis Index (WOMAC), Douleur Neuropathique en 4 Questions (DN4), and EuroQol-5 Dimensions (EQ-5D) at baseline and 1, 3, 6, and 9 months post-procedure.Results: By 6 months, 64% of patients showed ≥ 50% reduction in VAS pain scores, sustained at 9 months (p< 0.0001). Median WOMAC scores improved from 62.0 at baseline to 40.0 at 6 months (p< 0.0001). DN4 scores declined from a median of 4.0 at baseline to 2.0 at 6 months and 1.0 at 9 months (p< 0.001). EQ-5D scores demonstrated significant enhancement in quality of life (p< 0.01). Pain intensity differences at rest and during movement remained substantially improved at 9 months (p< 0.0001).Conclusion: GNRFA using a V-shaped active tip needle is a promising intervention for chronic knee pain, offering significant and sustained pain relief and functional improvement. Larger lesions created by the novel needle may overcome anatomical challenges, though further randomized studies are warranted to validate efficacy and safety.Keywords: chronic knee pain, chronic knee osteoarthritis, genicular nerve, pain management, radiofrequency ablation, neuromodulation